(untitled) (Research, Society and Development, 2023)
Objective: To identify the impact of integrative and complementary practices on nursing care. Methodology: This is an integrative literature review, carried out on the Scientific Electronic Library Online (SCIELO), Latin American and Caribbean Health Sciences Literature (LILACS) and PubMed databases. The guiding question was "What are the impacts related to the application of integrative practices in nursing care?". Results: The initial sample raised 123 articles due to the crossing of descriptors in the pre-established databases. These publications were then excluded according to the criteria established in the methodology. The study included 13 articles that answered the guiding question. Conclusion: Based on the information presented, it is clear that integrative and complementary practices have a positive impact on nursing care, providing a more holistic and comprehensive approach to meeting patients’ needs.